2013
DOI: 10.5539/jas.v5n5p15
|View full text |Cite
|
Sign up to set email alerts
|

Developing of Local Peanut Based on Multiculture That Tolerant to Abiotic and Biotic Conditions With Multigamma Radiation Method (Nuclear)

Abstract: The main problems investigated in these research are 1) the developing of local peanut variety from west Sumba through breeding with multigamma radiation method (nuclear) and carefully selection on two varieties of peanut, i.e erect peanut and creep peanut by multiculture principle, in order to obtain the primer seed of local peanut variety that can increase production, 2) developing of primer seed of local yellow corn, in order to tolerant to abiotic and biotic conditions. The main method of research is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some of the mathematical formulations required include (Pasangka & Refli, 2013a;Pasangka & Refli, 2013b;Pasangka & Refli, 2016;Pasangka & Irvandi, 2021).…”
Section: Statistics For Data Analysismentioning
confidence: 99%
“…Some of the mathematical formulations required include (Pasangka & Refli, 2013a;Pasangka & Refli, 2013b;Pasangka & Refli, 2016;Pasangka & Irvandi, 2021).…”
Section: Statistics For Data Analysismentioning
confidence: 99%
“…NNEA gives report that the mean production of kidney bean only 4,10 tons/ha and can be adapted to area with high calcium but was not adapted to dry conditions (NNEA, 2008). In other researchs (Pasangka and Jaelani, 2011;2013) on corn, peanut and soybean breeding, they found that the generations of those plants have the traits stably inherited up to 7 generations and after that the production to be more decreased. Agricultural land in Kupang Timor Island Indonesia was dominated by soil with high calcium, high salt and dry condition and also germ.…”
Section: The Range Production Average Production Increase Of Mean Pmentioning
confidence: 99%
“…The increase of mean production 43.86% for creep local peanut and 42.22% for erect local peanut, or mean production 5.7 tons/ha (from 3.2 tons/ha up to 5.7 tons/ha) for creep local peanut, production potential 5.9 tons/ha and 4.5 tons/ha (from 2.6-4.5 tons/ha) for erect local peanut, production potential 4.7 tons/ha (Pasangka and Jaelani, 2011).…”
Section: Radiation Effect On Dna and Chromosomementioning
confidence: 99%
See 1 more Smart Citation